Comparação de dois tipos de solução no posicionamento com receptores GPS - Dockhorn, Erika Silva (2006)
The basic principle of GPS use consists in the simultaneous measure of the distances between the receiver antenna and at least four satellites of the constellation. Known the distance from the satellite to the receiver antenna and the satellites coordinates, it is possible to calculate the user antenna coordinates in the same reference system of the satellites. The determination of X, Y, Z coordinates of the receiver antenna and the time (t) is done by the resolution of a equations system constituted by the same number of satellites, whose information be used at that time. The coordinates of the GPS receiver antenna can be calculated using two forms of solution: using the linearized formularization and using the exact formularization. This work has as objective to make a comparison between the absolute and relative positioning methods and their forms of solution: linearized and exact. To reach the proposed objectives one polygonal with nine vextexes was implanted in UFSM campus whose coordinates they had been determined by perimetrical path method using a Total Station. After, data collection of the each vertex with GPS receivers was performed. Later, data processing was carried out in the following way: for data processing in the linearized form Spectrum Survey software was used and for the processing in the exact form, a software was developed. The analysis of the results allowed to verify that data processing using the two solution forms are adequate to perform coordinates calculation once that they did not present significant difference when the two procedures were compared. When individually compared with the results supplied by the perimetrical path method using a Total Station, the exact solution showed to be more consistent than the linearized solution. The conclusion of this work is that the proposal methodology was able to supply the vertex coordinates presenting a way to carry out these calculations in a faster form and with the same reliability that the traditionally used method offers.